Dancing Beyond Democracy: Schooling Islam, Radicalism, And Moslem Citizenship Identity - Siti Qomala Khayati (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Abstract:This paper may be called as remarkable content and context of Islamic Educational Policy subjects; in term historical aspects, form of policies, and nowaday issues which are faced by many policy authority-makers. In short, Islamic educational policy as institutional reforms and developmentary aspects, migth included as a progresive point. Government had placed Islamic educational became a marginal institution and sub-system in national policies. Indeed, mainstreaming of Islamic Educational, had been prioriated at holistic aspect. Even if, in democratic era, these manstreamings often took out of from their frame suggestion. Such as, radicalism movement spreading out from Islamic and Educational institution. Like what had researched by Greg Fealy and Anthony Bubalo, Hefner, and another researchers. Therefore, this articles will discuss what had been reformed, its effects, and make new attention to build a conprehensive model of Islamic Educational, in democratic era. This article also will give futurological forcasting to what should be formulated as government decision. At least there are tree main-points will be remarked; first, reforming a curriculum design in national educational system. Second, arguing the moderate moslem as authentic identity of Indonesian People. Third, prosedural suggestion how to make and formulate a Islamic education to solve the issues.Keywords: Educational Policy, Islamic Education, and Citizenship Identity